Self-testing for contact allergy to hair dyes - a 5-year follow-up multicentre study - Friis, Ulrik F.; Goosens, An; Gimenez-Arnau, Ana M.; Liden, Carola; Gimenez-Arnau, Elena; White, Ian R.; Alfonso, Jose H.; Uter, Wolfgang; Johansen, Jeanne D. (Contact Dermatitis, 2018)
BACKGROUND: In 2011, a multicentre study was conducted in order to determine how hair dye manufacturers instructed consumers to perform a self-test prior to dyeing their hair, in order to identify individuals who are likely to react upon subsequent hair dyeing. A number of concerns were raised concerning the variability in instructions between products and producers, and the safety and validity of this tool. OBJECTIVES: To perform a 5-year follow-up study in order to determine whether manufacturers still recommend a self-test, and if so, whether the procedures have been changed. METHODS: During March 2016, a total of 40 oxidative hair dye products from 21 different manufacturers were bought in retail stores in 8 European countries. RESULTS: The consumers were instructed to perform a self-test prior to hair dyeing for 39 of the products; however, the procedures varied greatly regarding the method of application, the amount of hair dye applied, the location and size of the application area, the number of applications, whether or not rinsing was performed after application, the reading times, and how a positive reaction was defined. CONCLUSIONS: Self-testing is still recommended by almost all manufacturers of permanent hair dyes. There are major variations in the instructions, even in products from the same manufacturer. The previously raised concerns regarding safety and validity still remain.
EVALuna2:35691